Association of intense pulsed light and Erbium: Yag 2940 nm laser for treatment of lentigo on the face - Isadora Olenscki Gilli; Karina Bittencourt Medeiros; Juliana Merheb Jordão (Sociedade Brasileira de Dermatologia (SBD), 2020)
Solar lentigo is present in 90% of the population over 50 years of age andcharacterizes as hyperchromic spots in photoexposed regions. It increases with aging and is more frequent in light skin. There are several therapeutic modalities, which achieve better results whenassociated. We describe the case of a 62-year-old man with Fitzpatrick skinphototype II, complaining of brownish macules in nasal dorsum for eight years. The patient underwent a skin biopsy, and the histological study confirmed solar lentigo. The patient was treated with six sessions of Intense Pulsed Light associated with Erbium-Yag2940 nm Laser with a good clinical result.